Date | None Specimen | Marks available | 6 | Reference code | SPNone.1.hl.TZ0.12 |
Level | HL only | Paper | 1 | Time zone | TZ0 |
Command term | Deduce and Find | Question number | 12 | Adapted from | N/A |
Question
The matrix \(\boldsymbol{A}\) is given by \[\boldsymbol{A} = \left( {\begin{array}{*{20}{c}}
0&1&0\\
2&4&1\\
4&{ - 11}&{ - 2}
\end{array}} \right) .\]
(i) Find the matrices \({\boldsymbol{A}^2}\) and \({\boldsymbol{A}^3}\) , and verify that \({{\boldsymbol{A}}^3} = 2{{\boldsymbol{A}}^2} - {\boldsymbol{A}}\) .
(ii) Deduce that \({{\boldsymbol{A}}^4} = 3{{\boldsymbol{A}}^2} - 2{\boldsymbol{A}}\) .
(i) Suggest a similar expression for \({\boldsymbol{A}^n}\) in terms of \(\boldsymbol{A}\) and \({\boldsymbol{A}^2}\) , valid for \(n \ge 3\) .
(ii) Use mathematical induction to prove the validity of your suggestion.
Markscheme
(i) \({{\boldsymbol{A}}^2} = \left( {\begin{array}{*{20}{c}}
2&4&1 \\
4&7&2 \\
{ - 14}&{ - 26}&{ - 7}
\end{array}} \right)\) A1
\({{\boldsymbol{A}}^3} = \left( {\begin{array}{*{20}{c}}
4&7&2 \\
6&{10}&3 \\
{ - 24}&{ - 41}&{ - 12}
\end{array}} \right)\) A1
\(2{{\boldsymbol{A}}^2} - {\boldsymbol{A}} = 2\left( {\begin{array}{*{20}{c}}
2&4&1 \\
4&7&2 \\
{ - 14}&{ - 26}&{ - 7}
\end{array}} \right) - \left( {\begin{array}{*{20}{c}}
0&1&0 \\
2&4&1 \\
{ - 4}&{ - 11}&{ - 2}
\end{array}} \right)\) M1
\( = \left( {\begin{array}{*{20}{c}}
4&7&2 \\
6&{10}&3 \\
{ - 24}&{ - 41}&{ - 12}
\end{array}} \right) = {{\boldsymbol{A}}^3}\) AG
(ii) \({{\boldsymbol{A}}^4} = {\boldsymbol{A}}{{\boldsymbol{A}}^3}\) M1
\( = {\boldsymbol{A}}(2{{\boldsymbol{A}}^2} - {\boldsymbol{A}})\) A1
\( = 2{{\boldsymbol{A}}^3} - {{\boldsymbol{A}}^2}\)
\( = 2(2{{\boldsymbol{A}}^2} - {\boldsymbol{A}}) - {{\boldsymbol{A}}^2}\) A1
\( = 3{{\boldsymbol{A}}^2} - 2{\boldsymbol{A}}\) AG
Note: Accept alternative solutions that include correct calculation of both sides of the expression.
[6 marks]
(i) conjecture: \({{\boldsymbol{A}}^n} = \left( {n - 1} \right){{\boldsymbol{A}}^2} - \left( {n - 2} \right){\boldsymbol{A}}\) A1
(ii) first check that the result is true for \(n = 3\)
the formula gives \({{\boldsymbol{A}}^3} = 2{{\boldsymbol{A}}^2} - {\boldsymbol{A}}\) which is correct A1
assume the result for \(n = k\) , i.e. M1
\({{\boldsymbol{A}}^k} = (k - 1){{\boldsymbol{{\rm A}}}^2} - (k - 2){\boldsymbol{A}}\)
so
\({{\boldsymbol{A}}^{k + 1}} = {\boldsymbol{A}}\left[ {\left( {k - 1} \right){{\boldsymbol{A}}^2} - \left( {k - 2} \right){\boldsymbol{A}}} \right]\) M1
\( = \left( {k - 1} \right){{\boldsymbol{A}}^3} - \left( {k - 2} \right){{\boldsymbol{A}}^2}\) A1
\( = \left( {k - 1} \right)\left( {2{{\boldsymbol{A}}^2} - {\boldsymbol{A}}} \right) - \left( {k - 2} \right){{\boldsymbol{A}}^2}\) M1
\( = k{{\boldsymbol{A}}^2} - \left( {k - 1} \right){\boldsymbol{A}}\) A1
so true for \(n = k \Rightarrow \) true for \(n = k + 1\) and since true for \(n = 3\) ,
the result is proved by induction R1
Note: Only award the R1 mark if a reasonable attempt at a proof by induction has been made.
[8 marks]